The Role of Mosque In Education of Preschool Children (Study of some educational books for preschool children and mosque) - R.A Anggraeni Notosrijoedono (Universitas Islam Indonesia, 2011)
The existence of mosque is inseparable from the aspect of community education. Mosque can give various contributions, one of them in educating preschool children surrounding the mosque. Mosque comprises of various facilities of room and veranda can be used for various kinds of programs, one of them is education program for preschool students. Education for-preschool children initially is conducted in one of rooms or veranda of mosque, if it is organized kindly can develop and has its own building.One of the activities conducted for preschool children is Playing Group. The initial arrangement of Playing Group by some amount of students didn't need wide land, however more students follow the Playing Group it needs wide room and land. On the ground education for preschool children needs great number of games indoor and outdoor. Through the playing function, it can influence children's development, e.g. physical development i.e. hard and soft motoric competence, by playing, children's body will be more flexible. By conducting 49 kinds of funcationl playing In every Playing Group existing in mosque, hopeful the development in childhood of every child will be passed kindly.The total of mosque in Indonesia is 193.893 mosques by total of preschool children (0-6 years old) totalled 28.912.400 children, thus if every mosque is commanded to conduct Preschool Children Education hopeful twenty years later Indonesia will gain human resources who conduct their religion kindly, have good moral, smart and polite. Thus it needs cooperation between the policy maker of education for preschool children in Ministeriate of Religion and Ministeriate of National Education.